ANALISIS KARAKTERISTIK SPASIAL DAN TEMPORAL HOTSPOT DI TAMAN NASIONAL SEBANGAU PROVINSI KALIMANTAN TENGAH - Qadri, Muhammad Shaa Imul; Rusmayadi, Gusti; Priatmadi, Bambang Joko; Adriani, Dewi Erika (Universitas Lambung Mangkurat, 2023)
Sebangau National Park, in Central Kalimantan Province, is a wetland conservation area. In 2015, forest and land fires resulted in 455 hectares being burned. The identification of hotspots in this study is based on the number and distribution of hotspots based on satellite imagery data from the Moderate Resolution Imaging Spectroradiometer (MODIS) in 2001–2020. This study identifies hotspots by looking at the influence of rainfall and ENSO (El Nino Southern Oscillation) conditions. The method used is the method of spatial and temporal analysis. The aim of this study was to determine the characteristics of the hotspot distribution pattern in Sebangau National Park, Central Kalimantan Province, both spatially and temporally. There is a similarity between the temporal and spatial characteristics of hotspots in the number of significant additions to the number of hotspots in August, September, and October. The influence of monsoonal rainfall types and climates such as ENSO (El Nino Southern Oscillation) greatly influences the occurrence of hotspot events in Sebangau National Park, Central Kalimantan Province. The distribution pattern of hotspots in Sebangau National Park, Central Kalimantan Province, peaked in October, and the worst addition to the number of hotspots occurred in 2015, when these conditions occurred during the dry season and when the ENSO index (El Nino Southern Oscillation) showed +2.6, where these conditions included strong El Nino categories.